Oxygen-bridged adsorbed platinum-cobalt-phosphorus alloy material, preparation method and application thereof

CN116826090BActive Publication Date: 2026-10-27XIAMEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310800712.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2026-10-27
Estimated Expiration
2043-07-03

AI Technical Summary

Technical Problem

3d过渡金属元素可以有效地提高Pt的氧还原活性,但是考虑到过渡金属的溶解无法避免,过渡金属离子会置换Nafion膜中的质子,降低膜的电导率,严重影响电池性能

Benefits of technology

[0028]1、本发明的氧桥联吸附铂钴磷合金材料的晶格常数不发生膨胀,具有改善催化活性以及改善催化剂的稳定性的特点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116826090B_ABST
    Figure CN116826090B_ABST
Patent Text Reader

Abstract

The application discloses an oxygen bridging adsorption platinum-cobalt-phosphorus alloy material and a preparation method and application thereof, which is prepared from a platinum precursor, a cobalt precursor, benzyl alcohol, N,N-dimethylformamide, a carbon black carrier and a phosphorus-containing compound through a mixed reaction and heat treatment. The oxygen bridging adsorption platinum-cobalt-phosphorus alloy material has the characteristics of no lattice constant expansion, improved catalytic activity and improved stability of the catalyst. In the application, the platinum-cobalt-phosphorus alloy is loaded in a coordination mode with the carbon carrier doped with phosphorus oxygen functional groups, so that the agglomeration, migration and separation of nanoparticles can be effectively avoided. The application has good catalytic activity, can reduce the dosage of the catalyst and the cost when applied to a fuel cell cathode reaction, has good stability, can reduce the dissolution of platinum and phosphorus in the reaction process and prolong the service life of the fuel cell. Phosphate and other ions generated by the dissolution of phosphorus are more friendly to the transition metal ions, and the Nafion membrane is not damaged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fuel cell catalyst material technology, specifically relating to an oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material, its preparation method, and its application. Background Technology

[0002] Fuel cells are a new type of sustainable, efficient, and environmentally friendly energy conversion device. They directly convert the chemical energy of fuel into electrical energy. Both the cathode and anode of a fuel cell require highly active and stable catalysts.

[0003] Currently, the cathode catalysts used in fuel cells are mainly platinum and its alloys dispersed on a carbon black support. Compared to the relatively fast kinetics of the anode reaction, the kinetics of the oxygen reduction reaction at the cathode of a fuel cell are very slow, with an overpotential above 0.3 V. For proton exchange membrane fuel cells (PEMFCs) that use oxygen reduction as the cathode reaction, a large amount of the precious metal Pt needs to be loaded onto the cathode to achieve the rated output current. Currently, the Pt loading at the cathode in PEMFCs is still around 0.4 mg / cm³. 2 The loading of Pt at the anode is very low, approximately 0.05 mg / cm³. 2 .

[0004] Considering that Pt is currently the most efficient oxygen reduction catalyst in acidic media, improving the intrinsic activity of Pt is an effective way to reduce the Pt loading. Common solutions are: (1) reduce the particle size of Pt-based catalysts to improve dispersion and Pt utilization; (2) improve the intrinsic activity of Pt. 3d transition metal elements can effectively improve the oxygen reduction activity of Pt, but considering that the dissolution of transition metals is unavoidable, transition metal ions will replace protons in the Nafion membrane, reduce the membrane conductivity, and seriously affect the battery performance. In addition, some transition metals such as Fe and Cu ions will undergo Fenton reaction, destroying the structure of the Nafion membrane. Therefore, selective alloying of transition metals that do not undergo Fenton reaction is effective. (3) improve the durability of Pt-based alloy nanoparticles. Loaded Pt nanoparticles will agglomerate, migrate and separate, which is the main reason for low catalyst utilization and poor durability. The physical adsorption and confinement of common carbon supports cannot fully anchor the nanoparticles. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of existing technologies and provide an oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material.

[0006] Another object of the present invention is to provide a method for preparing the above-mentioned oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material.

[0007] Another object of the present invention is to provide the application of the above-mentioned oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material.

[0008] The technical solution of the present invention is as follows:

[0009] An oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material is prepared by mixing and reacting a platinum precursor, a cobalt precursor, benzyl alcohol, N,N-dimethylformamide, a carbon black carrier, and a phosphorus-containing compound, followed by heat treatment.

[0010] The platinum precursor includes at least one of platinum acetylacetonate, chloroplatinic acid, platinum(II) chloride, and potassium hypochloroplatinate.

[0011] Cobalt precursors include at least one of cobalt acetylacetonate, cobalt chloride hexahydrate, and cobalt nitrate hexahydrate;

[0012] The carbon black carrier includes at least one of Vulcan XC-72, Ketjen Black ECP-600JD, Ketjen Black ECP-300JD, and graphene;

[0013] Phosphorus-containing compounds include at least one of inositol hexaphosphate, phosphoric acid, hypophosphite, pyrophosphate, elemental phosphorus, and phosphine.

[0014] In a preferred embodiment of the present invention, the platinum precursor is platinum acetylacetonate.

[0015] In a preferred embodiment of the present invention, the cobalt precursor is cobalt acetylacetonate.

[0016] In a preferred embodiment of the present invention, the carbon black carrier is Ketjen Black ECP-600JD or Ketjen Black ECP-300JD.

[0017] In a preferred embodiment of the present invention, the phosphorus-containing compound is inositol hexaphosphate or phosphoric acid.

[0018] In a preferred embodiment of the present invention, the platinum precursor is platinum acetylacetonate, the cobalt precursor is cobalt acetylacetonate, the carbon black carrier is Ketjen Black ECP-600JD, and the phosphorus-containing compound is inositol hexaphosphate.

[0019] More preferably, the mass ratio of platinum acetylacetonate, cobalt acetylacetonate, and Ketjen Black ECP-600JD is 17-18: 18-19: 30.

[0020] The preparation method of the above-mentioned oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material includes the following steps:

[0021] (1) Disperse a platinum precursor, a cobalt precursor and benzyl alcohol in N,N-dimethylformamide and stir thoroughly;

[0022] (2) Add carbon black carrier to the material obtained in step (1) and treat it with ultrasound;

[0023] (3) Add inositol hexaphosphate solution to the material obtained in step (2) and mix thoroughly. Then pour it into an L high-pressure reactor and react at 165-175℃ for 15-17h.

[0024] (4) After centrifugation and vacuum drying, the material obtained in step (3) is heat-treated in an inert atmosphere to obtain the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material.

[0025] The above-mentioned oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material is used in the preparation of fuel cell cathode catalysts.

[0026] A fuel cell cathode catalyst, the raw materials of which include the above-mentioned oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material.

[0027] The beneficial effects of this invention are:

[0028] 1. The lattice constant of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material of the present invention does not expand, which has the characteristics of improving catalytic activity and improving catalyst stability.

[0029] 2. In this invention, the platinum-cobalt-phosphorus alloy is loaded in a coordinated manner with a carbon support doped with phosphorus and oxygen functional groups, which can effectively prevent the aggregation, migration and separation of nanoparticles.

[0030] 3. This invention has excellent catalytic activity. When applied to the cathode reaction of fuel cells, it can reduce the amount of catalyst used and reduce costs.

[0031] 4. This invention has excellent stability and can reduce the leaching of platinum and phosphorus during the reaction process, thus extending the life of the fuel cell.

[0032] 5. The phosphate ions produced by phosphorus dissolution in this invention are more compatible with transition metal ions and do not damage the Nafion membrane. Attached Figure Description

[0033] Figure 1 This is a schematic diagram of the structure of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in Example 1 of the present invention, wherein 1 and 2 are phosphorus atoms, 3, 4 and 5 are oxygen atoms, 6 is cobalt atoms, 7 is platinum atoms, and 8 is carbon atoms.

[0034] Figure 2 This is a flowchart illustrating the preparation of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material obtained in Example 1 of the present invention.

[0035] Figure 3 This is a schematic diagram of the formation path of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in Example 1 of the present invention.

[0036] Figure 4This is a transmission electron microscope comparison image of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in Example 1 of the present invention and a commercial Pt / C catalyst.

[0037] Figure 5 This is a comparison of the X-ray diffraction patterns of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in Example 1 of this invention and a commercial Pt / C catalyst.

[0038] Figure 6 The image shows a comparison of the X-ray photoelectron spectra of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in Example 1 of this invention and a commercial Pt / C catalyst.

[0039] Figure 7 This is an oxygen reduction polarization curve of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in Example 1 of the present invention and a commercial Pt / C catalyst.

[0040] Figure 8 This is a comparison of cyclic voltammetry curves before and after stability testing of the commercial Pt / C catalyst prepared in Example 1 of this invention.

[0041] Figure 9 This is a comparison of cyclic voltammetry curves before and after stability testing of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in Example 1 of this invention.

[0042] Figure 10 The diagram shows the oxygen reduction polarization curves of the PtCoP / C material prepared in Comparative Example 1 of this invention and a commercial Pt / C catalyst.

[0043] Figure 11 This is a comparison of the cyclic voltammetry curves before and after the stability test of the PtCoP / C material prepared in Comparative Example 1 of this invention.

[0044] Figure 12 The graph shows the oxygen reduction polarization curves of the PtCo / PC material prepared in Comparative Example 2 of this invention and the commercial Pt / C catalyst.

[0045] Figure 13 This is a comparison of the cyclic voltammetry curves before and after the stability test of the PtCoP / C material prepared in Comparative Example 2 of this invention. Detailed Implementation

[0046] The technical solution of the present invention will be further explained and described below with reference to specific embodiments and accompanying drawings.

[0047] Example 1

[0048] like Figure 2 As shown, the preparation of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material in this embodiment includes the following steps:

[0049] (1) Disperse 17.28 mg of platinum acetylacetonate, 18.73 mg of cobalt acetylacetonate and 75 μL of benzyl alcohol (reducing agent) in 30 mL of N,N-dimethylformamide and stir at 500 rpm for 0.5 h;

[0050] (2) Add 30 mg of Ketjen Black ECP-600JD to the material obtained in step (1) and sonicate for 2 hours (working frequency: 40KHz; ultrasonic power: 800W).

[0051] (3) Add inositol hexaphosphate solution (containing 13.21 mg of inositol hexaphosphate) to the material obtained in step (2) and mix thoroughly. Then pour it into a 50 mL high-pressure reactor and react at 170 °C for 16 h.

[0052] (4) After centrifugation and vacuum drying, the material obtained in step (3) is heat-treated at 200°C for 2 hours in an argon atmosphere (flow rate 40 sccm) to obtain the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material.

[0053] like Figure 1 As shown, in the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in this embodiment, oxygen atoms are inserted into the interstitial spaces of the platinum atom lattice. The lattice type of this oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material is the same as that of pure platinum, and the lattice constant is also basically the same as that of pure platinum. Here, "basically the same" means that when oxygen atoms are inserted into platinum atoms, the lattice constant will change slightly due to the size difference between the two atoms and the change in interatomic forces, but the overall lattice structure will not show obvious distortion. Figure 1 In this structure, atoms 1 and 2 represent phosphorus, 3, 4, and 5 represent oxygen, 6 represents cobalt, 7 represents platinum, and 8 represents carbon. In this structure, phosphorus atom 1 is bridged and adsorbed with cobalt atom 6 and platinum atom 7 via oxygen atom 3, thus mitigating metal leaching. Phosphorus atom 2 is bridged and adsorbed with the metal at the interface via oxygen atom 4, and with carbon atom via oxygen atom 5, preventing nanoparticle aggregation, migration, and separation.

[0054] The specific synthesis route of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material in this embodiment is as follows: Figure 3 As shown, under normal temperature and pressure, inositol hexaphosphate, in combination with a reducing agent, passes through... , , The path involves chelation with the metal, and then... , , The high-temperature, high-pressure hydrolysis process releases inositol, while the metal interacts with free electrons in ionic form to form metallic bonds, thereby forming a platinum-cobalt-phosphorus alloy. The resulting quaternary chelate ring greatly increases the stability of the metal ions.

[0055] The oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in this embodiment is compared with a commercial Pt / C catalyst (Johnson Matthey) using transmission electron microscopy. Figure 4 As shown, the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in this embodiment has a grain size that is essentially the same as that of pure platinum compared to the commercial Pt / C catalyst. Here, "essentially the same" means that after platinum is alloyed with the transition metal cobalt and the non-metal phosphorus, the nanoparticles do not show significant growth. Specifically, the grain size of the commercial Pt / C catalyst is approximately 2.8 nm; the grain size of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in this embodiment is approximately 3.1 nm.

[0056] The X-ray diffraction patterns of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in this embodiment are compared with those of commercial Pt / C catalysts. Figure 5 As shown, the position of the diffraction peak of the oxygen-bridged adsorbed platinum-cobalt-phosphorus alloy material prepared in this embodiment shifts positively compared to the commercial Pt / C catalyst, indicating that the lattice of the oxygen-bridged adsorbed platinum-cobalt-phosphorus alloy material prepared in this embodiment shrinks. Compared to the commercial Pt / C catalyst, the full width at half maximum (FWHM) of the diffraction peak of the oxygen-bridged adsorbed platinum-cobalt-phosphorus alloy material prepared in this embodiment does not change significantly.

[0057] The oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in this embodiment is compared with the X-ray photoelectron spectroscopy of a commercial Pt / C catalyst. Figure 6 As shown, the Pt 4f electron binding energy of the oxygen-bridged adsorbed platinum-cobalt-phosphorus alloy material prepared in this embodiment shows a positive shift compared to the commercial Pt / C catalyst. Specifically, compared to the commercial Pt / C catalyst, the electron binding energy of the oxygen-bridged adsorbed platinum-cobalt-phosphorus alloy material prepared in this embodiment is positively shifted by 0.57 eV. This indicates that the d-band center of the oxygen-bridged adsorbed platinum-cobalt-phosphorus alloy material prepared in this embodiment shifts downward, resulting in an improvement in the intrinsic activity of Pt during the ORR reaction.

[0058] The oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material obtained in this embodiment was formulated into a catalyst slurry. The preparation method of the catalyst slurry included: using an isopropanol aqueous solution (the volume ratio of isopropanol to water was 1:1) as a solvent, adding the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material to it until the concentration was 1 mg / mL, and adding 5 wt% Nafion solution at a ratio of 1 mg: 10 μL, and placing it in an ice-water bath for ultrasonication until uniform dispersion, thus obtaining the catalyst slurry.

[0059] 15 μL of the above catalyst slurry was uniformly dropped onto the surface of a rotating disk electrode to prepare a thin-film electrode, which was then used for electrochemical testing. Before the electrochemical test, the catalyst was subjected to cyclic voltammetry scans between 0 and 1.3 V (vs. RHE) until the curve stabilized, indicating activation was complete. Subsequently, electrochemical tests were performed in an oxygen-saturated 0.1 M perchloric acid solution, using a saturated calomel electrode as the reference electrode and a graphite rod as the counter electrode.

[0060] As a control, a comparative catalyst slurry was prepared from a commercial Pt / C catalyst for electrochemical testing. The preparation method of the comparative catalyst slurry included: using an isopropanol aqueous solution (the volume ratio of isopropanol to water was 1:1) as a solvent, adding the commercial Pt / C catalyst to it until the concentration was 1 mg / mL, and adding 5 wt% Nafion solution according to the ratio of the commercial Pt / C catalyst to 5 wt% Nafion solution of 1 mg: 10 μL, and placing it in an ice-water bath for ultrasonication until uniform dispersion.

[0061] 15 μL of the prepared comparative catalyst slurry was uniformly dropped onto the surface of a rotating disk electrode to prepare a thin-film electrode, which was then used for electrochemical testing. Before the electrochemical test, the catalyst was subjected to cyclic voltammetry scans between 0 and 1.3 V (vs. RHE) to clean the catalyst surface until the curve stabilized. Subsequently, the electrochemical test was performed in an oxygen-saturated 0.1 M perchloric acid solution, using a saturated calomel electrode as the reference electrode and a graphite rod as the counter electrode.

[0062] Test results are as follows Figure 7 As shown, the half-wave potential of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in this embodiment is 0.909 V, which is 25 mV more positive than the half-wave potential (0.884 V) of Johnson Matthey's commercial Pt / C catalyst. The kinetic current was calculated using the Koutecky-Levich equation, and then normalized using the electrochemical active area and the mass of Pt to obtain the area-specific activity (SA), mass-specific activity (MA), and electrochemical active area (ECSA), respectively. The area-specific activity of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in this embodiment is 2.98 mA / cm². 2 It is 14.9 times more potent than commercial Pt / C catalysts; its specific activity is 0.72 mA / μg. Pt It is 4.8 times that of commercial Pt / C catalysts, and its electrochemical active surface area is 24.0 m². 2 / g Pt .

[0063] To further evaluate the catalyst stability, cyclic voltammetry was performed for 30,000 cycles in an oxygen-saturated 0.1 M HClO4 solution, with a scan range of 0.6–1.0 V and a scan rate of 50 mV / s. After 30,000 cycles, the half-wave potential of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in this example shifted negatively by only 3 mV, while the commercial Pt / C catalyst shifted negatively by 8 mV. Correspondingly, the mass activity loss of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in this example was 24%, while that of the commercial Pt / C catalyst was 53%. After stability testing, the electrochemical area loss of the commercial Pt / C catalyst was 27.8%, as shown in the figure. Figure 8 As shown; however, the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material prepared in this embodiment only suffered a loss of 11.7%, as... Figure 9 As shown, the presence of phosphorus significantly inhibits the dissolution of Pt. Therefore, the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy catalyst prepared in this embodiment exhibits superior catalyst stability compared to commercial Pt / C catalysts.

[0064] Comparative Example 1

[0065] (1) 10.95 mg of platinum acetylacetonate, 7.9 mg of cobalt acetylacetonate and 69.3 μL of benzyl alcohol were dispersed in 20 mL of N,N-dimethylformamide and stirred at 500 rpm for 0.5 h.

[0066] (2) The material obtained in step (1) is transferred to a high-pressure reactor and reacted at 160°C for 12 h to obtain a PtCo suspension;

[0067] (3) 2.74 mg of platinum acetylacetonate, 1.97 mg of cobalt acetylacetonate, 0.61 mg of molybdenum hexacarbonyl and 1.92 μL of phytic acid were added to the above PtCo suspension. After stirring magnetically for 30 min, the mixture was transferred to a high-pressure reactor and reacted at 170 °C for 48 h to obtain PtCoP suspension.

[0068] (4) The above PtCoP suspension was mixed with 20 mg of carbon black (dispersed in 10 mL DMF), and ultrasonically treated for 2 h (working frequency: 40 KHz; ultrasonic power: 800 W). Then, it was washed three times with ethanol and acetone at 12000 rpm and washed once with deionized water. Then, it was dried in an oven at 70 °C for 30 min to collect the PtCoP / C material.

[0069] The PtCoP / C material was prepared into a comparative catalyst slurry, which was prepared in the same manner as in Example 1, and then subjected to electrochemical testing using the same method as in Example 1.

[0070] Test results are as follows Figure 10As shown, the area-to-body activity of the obtained PtCoP / C material is 2.4 mA / cm². 2 It is 10.91 times that of the commercial Pt / C catalyst; its specific activity is 0.61 mA / μg. Pt This is 4.1 times that of commercial Pt / C catalysts. After 30,000 scan cycles, the half-wave potential of the PtCoP / C material shifted negatively by only 3 mV, while that of the commercial Pt / C catalyst shifted negatively by 8 mV. Correspondingly, the mass activity loss of the PtCoP / C material was 16%; Figure 11 As shown, the electrochemical active area was reduced by only 13.1%, meaning that the presence of phosphorus significantly inhibited the dissolution of Pt. Therefore, the PtCoP / C catalyst exhibits superior catalyst stability compared to commercial Pt / C catalysts.

[0071] Comparative Example 2

[0072] (1) Disperse 100 mg Ketjen Black ECP-600JD in 30 mL of N,N-dimethylformamide and stir at 500 rpm for 0.5 h;

[0073] (2) Add inositol hexaphosphate solution (containing 15.53 mg of inositol hexaphosphate) to the material obtained in step (1) and mix thoroughly. Then pour it into a 50 mL high-pressure reactor and react at 180 °C for 16 h.

[0074] (3) The material obtained in step (2) is centrifuged and vacuum dried to obtain phosphorus-doped carbon (PC);

[0075] (4) Disperse 10.95 mg of platinum acetylacetonate, 7.9 mg of cobalt acetylacetonate and 82 μL of benzyl alcohol in 20 mL of N,N-dimethylformamide and stir at 500 rpm for 0.5 h;

[0076] (5) Add the above-mentioned PC to the material obtained in step (4) and ultrasonically treat for 2 hours (working frequency: 40KHz; ultrasonic power: 800W).

[0077] (6) Transfer the material obtained in step (5) to a 50 mL high-pressure reactor and react at 160 °C for 12 h;

[0078] (7) After centrifugation and vacuum drying, the material obtained in step (6) is heat-treated at 200°C for 2 hours in an argon atmosphere (flow rate 40 sccm) to obtain PtCo / PC material;

[0079] The PtCo / PC material was used to prepare a comparative catalyst slurry, which was prepared in the same manner as in Example 1, and was subjected to electrochemical testing using the same method as in Example 1.

[0080] Test results are as follows Figure 12 As shown, the area-to-body activity of the obtained PtCo / PC material is 1.74 mA / cm². 2 It is 8.7 times more potent than commercial Pt / C catalysts; its specific activity is 1.11 mA / μg. Pt It is 7.4 times that of commercial Pt / C catalysts, and its electrochemical active surface area is 67.5 m². 2 / g Pt The difference from commercial Pt / C catalysts is only slight. After 30,000 scan cycles, the half-wave potential of the PtCo / PC material shifted negatively by only 3 mV, while the commercial Pt / C catalyst shifted negatively by 8 mV. Correspondingly, the mass activity loss of the PtCo / PC material is 24%; Figure 13 As shown, the electrochemical active area was only lost by 11.9%, meaning that PC as a support can effectively inhibit the aggregation, migration, and separation of nanoparticles. Therefore, the catalytic activity and stability of the PtCo / PC material are superior to those of commercial Pt / C catalysts.

[0081] The above description is merely a preferred embodiment of the present invention, and therefore should not be construed as limiting the scope of the present invention. All equivalent changes and modifications made in accordance with the scope of the patent and the contents of the specification should still fall within the scope of the present invention.

Claims

1. An oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material, characterized in that: It is prepared by mixing and reacting a platinum precursor, a cobalt precursor, benzyl alcohol, N,N-dimethylformamide, carbon black support, and a phosphorus-containing compound, followed by heat treatment. The specific steps include: (1) Disperse a platinum precursor, a cobalt precursor and benzyl alcohol in N,N-dimethylformamide and stir thoroughly; (2) Add carbon black carrier to the material obtained in step (1) and treat it with ultrasound; (3) Add inositol hexaphosphate solution to the material obtained in step (2) and mix thoroughly. Then pour it into a high-pressure reactor and react at 165-175℃ for 15-17h. (4) After centrifugation and vacuum drying, the material obtained in step (3) is heat-treated in an inert atmosphere to obtain the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material. in, Platinum precursors include at least one of platinum acetylacetonate, chloroplatinic acid, and platinum(II) chloride; Cobalt precursors include at least one of cobalt acetylacetonate, cobalt chloride hexahydrate, and cobalt nitrate hexahydrate; The carbon black carrier includes at least one of Vulcan XC-72, Ketjen Black ECP-600JD, and Ketjen Black ECP-300JD; Phosphorus-containing compounds include inositol hexaphosphate.

2. The oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material as described in claim 1, characterized in that: The platinum precursor is platinum acetylacetonate.

3. The oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material as described in claim 1, characterized in that: The cobalt precursor is cobalt acetylacetonate.

4. The oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material as described in claim 1, characterized in that: The carbon black carrier is either Ketjen Black ECP-600JD or Ketjen Black ECP-300JD.

5. The oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material according to any one of claims 1 to 4, characterized in that: The platinum precursor is platinum acetylacetonate, the cobalt precursor is cobalt acetylacetonate, the carbon black carrier is Ketjen Black ECP-600JD, and the phosphorus-containing compound is inositol hexaphosphate.

6. The oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material as described in claim 5, characterized in that: The mass ratio of platinum acetylacetonate, cobalt acetylacetonate, and Ketjen Black ECP-600JD is 17-18: 18-19:

30.

7. The application of the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material according to any one of claims 1 to 6 in the preparation of fuel cell cathode catalysts.

8. A cathode catalyst for a fuel cell, characterized in that: Its raw materials include the oxygen-bridged adsorption platinum-cobalt-phosphorus alloy material as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Nitrogen-phosphorus co-doped carbon-loaded platinum-cobalt-based nano-alloy catalyst as well as preparation method and application thereof

    CN112490453A

  • Platinum-cobalt alloy carbon catalyst for proton exchange membrane fuel cell and preparation method of platinum-cobalt alloy carbon catalyst

    CN113540481A